Using Social Media for Online English Assignments: Problems and Solutions - Marisa Fran Lina (Siliwangi University, 2021)
Social media are widely used in today’s activities for all levels of humans. In students’ daily activities, updating their status through social media is like a must. Thus, the writer wants to highlight her teaching activity to something that her students love doing in it. English and social media become her concern to write this paper. Therefore, the aim of this research is to find out the kind and examples of vocabulary learned and appropriate grammar that appear in the students’ social media during this online learning era. She will also tell the steps, challenges and solutions based on her English teaching experience. The method is qualitative research, by finding, describing and analyzing the data in students’ social media after online learning English. The data shows that many students apply correct grammar, but only a few students use vocabularies learned from online class to update their status in social media. Besides, the lecturer provides some suggestions to fix their errors in using the words in a sentence. This research is supported by other relevant studies about the advantage of social media in learning and it tries to contribute ideas toward different opinions from other researchers. The findings also more detailed on the use of correct English grammar and vocabulary in social media.